Implementation of General Election Commission Regulations in Realizing Data Updating in East Kalimantan Province - Kusuma, Aji Ratna; Saipul, Saipul; Sarifudin, Sarifudin; Cornelia, Geby; Rahim, Muhammad Nur (LEGAL BRIEF, 2025)
The General Election Commission as an institution authorized to organize elections transparently, accountably, and in accordance with legal provisions. The accuracy and precision of data is a central element that determines the quality and fairness of elections. The KPU plays a role in ensuring that every citizen exercises their voting rights through a structured and tiered data updating process. This study aims to analyze the implementation of General Election Commission Regulation Number 7 of 2023 using the implementation model according to Edward III including communication, resources, disposition, and bureaucratic structure and see the inhibiting factors of its implementation. This research uses a qualitative descriptive method. The results showed that the implementation of KPU regulations has not run optimally in realizing data updating in East Kalimantan Province. There are findings in matching and research that clearly violate and are not in accordance with established regulations. This has an impact on the inaccuracy of the Permanent Voters List data. The KPU of East Kalimantan Province endeavors in the process of updating the DPT as the basis for election calculations. This accurate data certainly leads to transparency and minimizes the potential for fraud in the 2024 elections.